ARE THERE ANY PROGRAMMES LINKING PHYSICAL EDUCATION AND NUTRITION AT THE FACULTY OF CHEMICAL AND FOOD TECHNOLOGY? (Fiep Bulletin - online, 2014)
Despite the chemical and technological character of the Faculty of Chemical and Food Technology (FCHFT , est. in 1939), history of this institution includes important activities of various representatives of Physical education in Slovakia. Perhaps the most famous personalities of the Department of Physical Education at the former Faculty of Chemical Technology were Assoc. Prof. Dr. Jozef Vengloš, (former Czechoslovak football player, coach and manager) and Dr. Mária Mra?nová, (the medallist of the European Athletics Championships in 1969 and finalist of two Olympic Games in high jump discipline). At present, both they are the honorary members of the Slovak Olympic Committee at present. Within the lecture presented at the 8th FIE P European Congress, we would like to provide the information on our present pedagogical and research activities carried out at the Faculty of Chemical and Food Technology that are connected with physical and nutritional education of the students. We also focus on some physiological or nutritional benefits connected with balanced diet and foods with added values, e.g. with probiotic effects. From the current projects of our department, a four month long intervention study was realized in cooperation with the Department of Physical Education (FCHFT ) in cooperation with Slovak Medical University. The research was aimed to test the effectiveness of newly designed dance programme combined with nutritionally balanced diet and functional cereal drink consumption as a tool for civilisation disease prevention. A significant improvement was seen in the monitored anthropometric and biochemical parameters what may play an important role in the process of enhancing the general quality of life, covering not only faculty students but also adult population. Moreover, our department has participated on the realisation of EU project “Health effects of plant food and the possibility of reduction of health risks” in the cooperation with Slovak M edical University. Differences in qualitative and quantitative composition of gut microbiota of vegetarians and non-vegetarians were studied within the project. Besides publications in scientific journals, the outputs of this cooperation were the conference “Nutrition in the civilisation disease prevention” and a brochure concluding all the project results aimed not only for experts but also for general population, To the new priorities of our faculty belongs also the connection of the research and education in the field of nutrition with exercise and physical education which should create a base of the high quality and healthy life. Since there are no specialized programmes integrating nutrition, sports and health on the Slovak universities, our aim is to create a new specialisation in the collaboration with the Faculty of Physical Education and Sports (Comenius University in Bratislava) covering the interests of physically active general population, in contrast to highly profiled sports nutrition concentrated more on sports professionals.
Keywords: physical education programmes; nutrition; probiotics